Regionalno in prostorsko planiranje ali regionalno-prostorsko planiranje - Naprudnik, Milan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
On the basis of necessities to connect different aspects of sectoral planning in the 60-ies of last century, regional-spatial planning was developed. In 1970 -1975 Slovenia elaborated basic professional elements for adoption of regional-spatial plan of the republic. With the transition to the system of social planning a process of general guidance were adopted, which were also continuing for ten years in the time independent state. Strategy of spatial development was adopted not until the year 2002, but without clarifying the relationships between the strategy of regional development at the national level and with the guidelines at the European level.
Keywords: prostorsko planiranje; spatial planning; regionalno planiranje; regionalni razvoj; Slovenia; Slovenija